Pemberdayaan Anak Jalanan Kota Pangkalpinang Dalam Upaya Pengembangan Karakter, Kreativitas Serta Minat Baca Melalui Program Pendidikan Nonformal - Fiki Arianti (Indonesian Journal of Dedication and Educations, 2023)
The development of the number of street children which is increasing every year needs attention from various parties. The existence of street children is motivated by several factors including poverty, less harmonious families, victims of urbanization, environmental conditions to personality deviations. In general, the main factor that triggers the existence of street children is the factor of poverty, so that in meeting their daily needs they have to take to the streets to make a living. Education is no longer the most important thing, considering the conditions they are currently facing. Economic difficulties make street children have to give up their education and focus on fulfilling their daily needs. Therefore this empowerment program is designed to facilitate street children to regain their right to receive education. The implementation of this program uses a method of approach and assistance in developing character, creativity and interest in reading through non-formal education programs such as organizing creativity classes, book stalls and watching educational films. The target of this empowerment program is street children at several red light intersection points in the center of Pangkalpinang City. The implementation of this program collaborates with related parties who deal with social problems,namely the Pangkapinang City Social Service and the Bangka Rapid Response Agency which is engaged in social and humanitarian fields.